The crystal structure of ethyl 5,6-dihydroxybenzofuran-3-carboxylate, C11H10O5 - Zhou Ying; Li Yan; Xiao Zengshuo; Wang Hao (Zeitschrift für Kristallographie - New Crystal Structures)
C11H10O5, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 8.9847(3) Å, b = 10.5228(3) Å, c = 11.2032(4) Å, α = 106.484(3)°, β = 93.420(3)°, γ = 103.646(3)°, V = 977.84(6) Å3, Z = 4, R gt(F) = 0.0441, wR ref(F 2) = 0.1298, T = 293 K.